Perancangan Sistem Informasi Akademik Sekolah Berbasis Web Studi Kasus SMK Wira Harapan - Mirela, Marshanda Cindy (Jurnal Sistem Informasi dan Komputer Terapan Indonesia (JSIKTI), 2022)
Web-Based Academic Information System at Wira Harapan Vocational School is a system that provides online student activity reports in the form of web-based student attendance reports, thus helping speed and quality in delivering information. In addition, by being web-based, data information can be accessed at an unspecified time and place. In this system, the menu can only be accessed by certain users, namely students, teachers and administrators. The results of this study have developed a Web-Based Academic Information System with a case study at Wira Harapan Vocational School. Where in building this system used system development tools, namely Data Flow Diagrams (DFD), Context Diagrams, Entity Relationship Diagrams (ERD) and Flowcharts as well as using PHP and HTML programming languages ​​and MySQL as databases. Keywords—Academic, System Information